KAJIAN POTENSI PRODUKSI PADI SERTA EVALUASI KINERJA OPERASI DAN PEMELIHARAAN SISTEM IRIGASI BANDAR DOLOK DI KECAMATAN PAGAR MERBAUKABUPATEN DELI SERDANG (The Study of Rice Potential Production with The Operational Work Evaluation and Maintenance of Bandar - Muhammad Iqbal Tanjung; Sumono Sumono; Riswanti Sigalinggling (Universitas Sumatera Utara, 2018)
ABSTRACT Bandar Dolok is a rice production area in Deli Serdang Regency which served by technical irrigation system with rice productivity target that can reach its production potential. The achievement of the targetwas evaluated based on production target and operation performance and maintenance of irrigation system in the period of 2011-2015. Some of the research indicators were potential production, productivity, production target, and rice landscaping indices and operation performance and maintenance of irrigation system. The results showed that the average of potential production was 9,18 ton/ha, the average of productivity was 5,78 ton/ha, the average of production target was 69,933%, rice landscaping indices were 2 and performance of operation and maintenance of irrigation system was 2,97; that could be classified in the well category. Keywords: Rice, Production Potential, Performance Evaluation, Irrigation System, Bandar Dolok. ABSTRAK Bandar Dolok merupakan daerah penghasil beras di kabupaten Deli Serdang yang dilayani oleh sistem irigasi teknis dengan target produktivitas padi yang dihasilkan dapat mencapai potensi produksinya. Ketercapaian target tersebut dievaluasi berdasarkan aras pencapaian produksi padi serta kinerja operasi dan pemeliharaan sistem irigasinya pada periode 2011 – 2015. Beberapa indikator penelitiannya adalah potensi produksi, produktivitas, aras pencapaian produksi dan indeks pertanaman padi serta kinerja operasi dan pemeliharaan sistem irigasi. Hasil penelitian menunjukkan potensi produksi rata – rata adalah 9,18 ton/ha, produktivitas rata – rata 5,78 ton/ha, aras pencapaian produksi rata – rata 69,933%, indeks pertanaman padi 2 serta kinerja operasi dan pemeliharaan sistem irigasi mencapai score 2,97 tergolong dalam kategori baik. Kata Kunci : Padi, Potensi Produksi, Evaluasi Kinerja, Sistem Irigasi, Bandar Dolok.